Influence of particle size and tunable interactions on isotropic–nematic transition of block copolymer single crystal platelet suspensions - Jiang, Chunbo; Huang, Haiying; Ma, Cungui; He, Tianbai; Zhang, Fajun (Academic Press, 2013)
We have studied the influence of the particle size and the tunable lateral interactions on the isotropic–nematic (I–N) phase transition of a plate-like colloidal system. The particles are single crystals of a block copolymer PS-b-PLLA (BCSC) prepared using a self-seeding procedure. These lozenge shape crystals have a uniform thickness and a narrowly distributed lateral size. The equilibrium phase behavior and I–N phase transition have been characterized using crossed polarizers at the room temperature. A nematic phase exists for all systems with size ranging from 700 to 4000 nm. For smaller crystals (<1200 nm), the I–N phase transition follows a process of slow sedimentation and subsequent macroscopic phase separation, resulting in a highly oriented nematic phase with a sharp I–N interface. For larger crystals (≥1200 nm), the I–N phase transition follows a process of nucleation and subsequent sedimentation, resulting in a random orientation of crystals in the nematic phase and a rough I–N interface. The I–N transition occurs at a very low volume fraction (<0.2%) for all systems, which is at least one order of magnitude lower than the theoretical prediction (2–7%). However, addition of a small amount of ethanol into the solution, the I–N transition can be significantly suppressed. These results demonstrate the existence of a lateral attraction between crystals, which is due to the polar attraction between the uncovered PLLA crystalline domains. Polar ethanol molecules can adsorb to the PLLA crystalline surface and screen the attraction. The attraction exhibits highly orientation-dependent. To further demonstrate this highly directional attraction, we have prepared two composite single crystal suspensions with PLLA homopolymer, which have a much wider open angle for the polar attraction. Indeed, the resulting liquid crystalline phases show much less horizontal ordering.